Guidance for evaluating biomaterials’ properties and biological potential for dental pulp tissue engineering and regeneration research - Vinicius, Rosa; Neves, Cavalcanti Bruno; E., Nör Jacques; Tezvergil-Mutluay, Arzu; Nikolaos, Silikas; C., Bottino Marco; Anil, Kishen; Gabriela, Soares Diana; M., Franca Cristiane; Roy, Cooper Paul; F., Duncan Henry; L., Ferracane Jack; et al. (Elsevier, 2025)
Background
Dental pulp regeneration is a complex and advancing field that requires biomaterials capable of supporting the pulp’s diverse functions, including immune defense, sensory perception, vascularization, and reparative dentinogenesis. Regeneration involves orchestrating the formation of soft connective tissues, neurons, blood vessels, and mineralized structures, necessitating materials with tailored biological and mechanical properties. Numerous biomaterials have entered clinical practice, while others are being developed for tissue engineering applications. The composition and a broad range of material properties, such as surface characteristics, degradation rate, and mechanical strength, significantly influence cellular behavior and tissue outcomes. This underscores the importance of employing robust evaluation methods and ensuring precise and comprehensive reporting of findings to advance research and clinical translation.
Aims
This article aims to present the biological foundations of dental pulp tissue engineering alongside potential testing methodologies and their advantages and limitations. It provides guidance for developing research protocols to evaluate the properties of biomaterials and their influences on cell and tissue behavior, supporting progress toward effective dental pulp regeneration strategies